Integrated Taxonomic Approaches to Gastrointestinal and Urinary Capillariid Nematodes from Wild and Domestic Mammals - Masae Tamaru; Seiho Sakaguchi; Yasuhiro Souzu; Koichi Murata; Muchammad Yunus; Imron Rosyadi; Hiroshi Sato (Pathogens)
Fine nematodes of the family Capillariidae parasitize various organs and tissues in fish, amphibians, reptiles, avians, and mammals. Currently classified into more than 20 genera, these nematodes are primarily distinguished based on the caudal structures of male worms. Morphological and molecular analyses were conducted on 15 mammal-parasitic species belonging to the genera Aonchotheca (A. putorii, A. suzukii n. sp., A. suis n. comb. (syn. Capillaria suis), A. riukiuensis, and A. bilobata), Pearsonema (P. neoplica n. sp., P. feliscati, P. iharai n. sp., and P. toriii n. sp.), Liniscus (L. himizu), Calodium (C. hepaticum), Echinocoleus (E. yokoyamae n. sp.), and Eucoleus (E. kaneshiroi n. sp., E. aerophilus, and Eucoleus sp.), using specimens from various wild and domestic animals in Japan and brown rats in Indonesia. As demonstrated in this study, nearly complete SSU rDNA sequencing is a powerful tool for differentiating closely related species and clarifying the phylogenetic relationships among morphologically similar capillariid worms. Additionally, most capillariid worms detected in dogs and cats are suspected to be shared with their respective wildlife reservoir mammals. Therefore, molecular characterization, combined with the microscopic observation of these parasites in wildlife mammals, provides a robust framework for accurate species identification, reliable classification, and epidemiological assessment.